Method for in-situ preparation of boron nitride nano material for metal reinforcement on surface of metal composite microsphere

By preparing boron nitride nanomaterials in situ on the surface of nickel-clad aluminum microspheres, the problems of agglomeration and segregation of boron nitride nanotubes in metal matrix are solved, and its good dispersion and strength improvement in metal-based composite materials are achieved.

CN119772172APending Publication Date: 2025-04-08CHINA NORTH ENGINE INST TIANJIN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510048850.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Boron nitride nanotubes are prone to agglomeration and segregation in metal matrix, resulting in poor dispersion in metals, increasing the difficulty of casting and preparation of metal-based composite materials.

Method used

Boron nitride nanomaterial is prepared in situ on the surface of nickel-clad aluminum microspheres. The nickel-clad aluminum microspheres are heated in an inert gas, and mixed gas of boron source and alcohol source are passed into boron dehydration. Then, high-temperature annealing is performed in the mixed gas containing ammonia to prepare a composite material of boron nitride nanosheets and nanotubes, and a nanotitanium metal plating is deposited on the surface, and finally annealed in the inert gas to obtain boron nitride nanomaterial for metal reinforcement.

Benefits of technology

Through this method, the agglomeration of boron nitride nanotubes in the metal matrix can be significantly reduced, and its good dispersion can be achieved, and the strength of the metal-based composite material can be significantly improved under low addition conditions, while maintaining good elongation and other properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119772172A_ABST
    Figure CN119772172A_ABST
Patent Text Reader

Abstract

The invention provides a method for in-situ preparation of a boron nitride nano-material for metal reinforcement on the surface of a metal composite microsphere, which comprises the following steps: S1, heating nickel-coated aluminum microspheres in inert gas, and introducing mixed gas of a gas boron source and a gas alcohol source to obtain boronized nickel-coated aluminum microspheres; s2, stirring the boronized nickel-coated aluminum microspheres to obtain nickel-coated aluminum microspheres from which the exfoliated boron source is removed; s3, high-temperature annealing is carried out in mixed gas containing ammonia gas, and a composite material of the boron nitride nanosheets and the boron nitride nanotubes is prepared; and S4, a nano titanium metal coating is deposited on the surface in situ, then aluminum powder is added, the mixture is pressed into particles, annealing is conducted in inert gas, and the boron nitride nano material for metal enhancement is obtained. The boron nitride nanotube and boron nitride nanosheet composite tube prepared by the invention has particle reinforcement and short fiber reinforcement at the same time, and can realize various reinforcement effects of grain refinement, dislocation reinforcement, second phase reinforcement and the like in the aluminum alloy casting process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano ceramic materials, and in particular relates to a method for in-situ preparing boron nitride nano material for metal reinforcement on the surface of metal composite microspheres. Background Art

[0002] Boron nitride nanotubes (BNNT) have a structure similar to carbon nanotubes. They have excellent thermal conductivity and mechanical properties like carbon nanotubes (CNTs), but have better thermal stability than carbon nanotubes. The density of boron nitride nanotubes is only 1 / 6 of that of steel, but its tensile strength is 100 times that of steel. Although CNTs have performed significantly in the field of metal reinforcement, they have poor thermal stability, are easy to agglomerate, are difficult to disperse, and are easy to form brittle nanoceramic interfaces such as Al4C3 at the metal Al interface, making it difficult to achieve metal stress transfer. Boron nitride nanotubes form an AlN interface with moderate strength in aluminum metal and have good wettability at the aluminum interface. At present, the academic community generally believes that boron nitride nanotubes are nanoceramic reinforcement phases with better comprehensive performance than CNTs, and are expected to be used to prepare the most outstanding aluminum, titanium and magnesium metal reinforcement materials in the future.

[0003] At present, boron nitride nanotubes as a reinforcement phase in the metal matrix can significantly inhibit the growth of metal grains, prevent the slip of dislocations, and increase the density of dislocations, which is of great significance for improving the strength of metal materials. However, since boron nitride nanotubes are nanoscale, the aspect ratio is relatively large, and the agglomeration is more obvious. When boron nitride nanotubes are added to metals, the nanotubes are prone to agglomeration and segregation due to the large capillary tension, which is the key technical problem that CNT and boron nitride nanotubes are difficult to apply on a large scale. In addition, when boron nitride nanotubes come into contact with aluminum liquid, they react to form a nanoscale interface layer. In order to solve the agglomeration and segregation of boron nitride nanotubes in the metal matrix, methods of surface modification of boron nitride nanotubes are often used, such as using PVD to deposit nickel and aluminum coatings on the surface of boron nitride nanotubes. Or methods of chemical group modification on the surface of boron nitride nanotubes can solve the agglomeration of boron nitride nanotubes. Or auxiliary methods such as ultrasound and stirring are added during the casting process to prevent the agglomeration and segregation of boron nitride nanotubes. However, the above methods make the preparation process of metal matrix composite materials more complicated, and it is difficult to fundamentally solve the technical problem of poor dispersion of boron nitride nanotubes in the metal matrix, which increases the difficulty of casting preparation of metal matrix composite materials. Summary of the invention

[0004] In view of this, the present invention aims to provide a method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres to solve at least one technical problem in the background technology.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows: A method for in-situ preparation of boron nitride nanomaterials for metal reinforcement on the surface of metal composite microspheres comprises the following steps: S1: The nickel-coated aluminum microspheres are heated in an inert gas, and a mixed gas of a gaseous boron source and a gaseous alcohol source is introduced to obtain boronized nickel-coated aluminum microspheres; S2: stirring the boronized nickel-coated aluminum microspheres obtained in step S1 to obtain nickel-coated aluminum microspheres from which the boron source has been removed; S3: annealing the nickel-coated aluminum microspheres obtained in step S2 with the boron source removed at high temperature in a mixed gas containing ammonia to prepare a composite material of boron nitride nanosheets and boron nitride nanotubes; S4: in situ depositing a nano-titanium metal coating on the surface of the composite material of boron nitride nanosheets and boron nitride nanotubes obtained in step S3 to obtain a composite material of boron nitride nanosheets and boron nitride nanotubes with a titanium layer, adding aluminum powder and pressing into particles, and annealing in an inert gas to obtain a boron nitride nanomaterial for metal reinforcement.

[0006] Furthermore, in step S1, the particle size of the nickel-coated aluminum microspheres is 50-500 μm, the thickness of the nickel layer is 10 μm, and the morphology of the nickel-coated aluminum microspheres is spherical.

[0007] Furthermore, the inert gas in step S1 is argon, and the argon pressure ranges from 0.01 to 0.1 MPa; And / or, the heating temperature in step S1 is 750-950° C.; And / or, the molar ratio of the gaseous boron source to the gaseous alcohol source in step S1 is 1:1.5-2.5.

[0008] Further, the boron source in step S1 includes one or both of BCl3 and ammonia borane. Preferably, the boron source is BCl 3。

[0009] And / or, the gaseous alcohol source in step S1 includes one or more of methanol, ethanol, and propanol. Preferably, the gaseous alcohol source is methanol.

[0010] Furthermore, in step S2, the stirring speed of the nickel-coated aluminum microspheres after boronization is 50 to 300 rpm, and the stirring time is 30 to 60 s; And / or, the mixed gas containing ammonia in step S3 includes ammonia and an inert gas, and the inert gas includes one or more of nitrogen, hydrogen, and argon; And / or, the annealing temperature of the high temperature annealing in step S3 is 900-1500° C., and the annealing time is 5.5-6.5 hours.

[0011] Furthermore, in the composite material of boron nitride nanosheets and boron nitride nanotubes prepared in step S3, the length of the boron nitride nanotubes is 50-100 μm; preferably, the length of the boron nitride nanotubes is 100 μm.

[0012] The diameter of the boron nitride nanotubes in the composite material of boron nitride nanosheets and boron nitride nanotubes prepared in step S3 is 150-200 nm.

[0013] The wall thickness of the boron nitride nanotubes in the composite material of boron nitride nanosheets and boron nitride nanotubes prepared in step S3 is 30-80 nm, preferably 10 nm, and the median diameter of the boron nitride nanotubes is 150-200 nm, preferably 150 nm.

[0014] And / or, the lateral length of the boron nitride nanosheets in the composite material of boron nitride nanosheets and boron nitride nanotubes prepared in step S3 is 20-50 nm, preferably, the lateral length is 20 nm.

[0015] The thickness of the boron nitride nanosheet is 10-20 nm, and preferably, the thickness of the boron nitride nanosheet is 10 nm.

[0016] Furthermore, in step S4, the titanium layer thickness of the composite material of boron nitride nanosheets and boron nitride nanotubes having a titanium layer is 5 to 15 nm; And / or, the mass of the aluminum powder in step S4 is 50-90% of the mass of the composite material of boron nitride nanosheets and boron nitride nanotubes having a titanium layer; And / or, the pressure of pressing the granules after adding the aluminum powder in step S4 is 2 to 10 MPa; And / or, the inert gas in step S4 is argon; And / or, the annealing temperature in the inert gas in step S4 is 650-800°C.

[0017] Compared with the prior art, the method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres described in the present invention has the following advantages: 1. The present application utilizes a nickel-coated aluminum carrier to in-situ grow boron nitride nanotubes loaded with boron nitride nanosheets on the carrier surface, and utilizes a low-cost magnesium thermal reduction boron oxide reaction system as a raw material. In an ammonia atmosphere, by reasonably regulating the reaction process parameters, the two reactions of liquid phase growth of boron nitride nanosheets and vapor phase growth of nanotubes are maintained to occur simultaneously.

[0018] 2. The present application regulates the growth ratio of boron nitride nanosheets and nanotubes within the temperature range, and synthesizes a boron nitride nanotube with a large amount of boron nitride nanosheets enriched and grown on the surface in one step. At the same time, the difference in thermal expansion coefficients of nickel and aluminum is utilized to grow highly dispersed boron nitride nanosheets and boron nitride nanotube composite nanotubes on the surface. On the one hand, the boron nitride nanotubes with a large amount of boron nitride nanosheets on the surface can significantly reduce the agglomeration in the casting of liquid metal aluminum liquid. On the other hand, the boron nitride nanosheets on the surface of the boron nitride nanotubes participate in the interfacial reaction in the aluminum liquid to generate nano-scale titanium boride, aluminum boride and aluminum nitride nanoparticles in situ, which has the effect of refining grains and achieving the strengthening effect of the metal matrix, while avoiding a large amount of burning of nanotubes, and can achieve the synergistic enhancement of nanoparticles and nanotubes. The boron nitride nanotubes and boron nitride nanosheet composite tubes prepared by this method have good uniformity, can avoid agglomeration in aluminum liquid, have good dispersion in aluminum liquid, and simultaneously achieve particle reinforcement and short fiber reinforcement, achieving a significant improvement in the strength of metals such as aluminum alloys under low addition conditions while maintaining good elongation of the aluminum alloy matrix.

[0019] 3. The boron nitride nanotube and boron nitride nanosheet composite tube prepared in this application has both particle reinforcement and short fiber reinforcement, and can achieve multiple strengthening effects such as grain refinement, dislocation reinforcement, and second phase strengthening during the aluminum alloy casting process, and can achieve a significant improvement in the strength of metal matrices such as aluminum alloys while maintaining a high elongation under low addition conditions, and has good neutron absorption resistance and high temperature creep resistance. The aluminum alloy composite material strengthened by the composite nanotube. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings: Figure 1 This is a SEM image of the composite material of boron nitride nanosheets and boron nitride nanotubes shown in Example 1 of the present invention (the electron microscope magnification of a is 200,000 times, and the electron microscope magnification of b is 100,000 times); Figure 2 The structural schematic diagram and SEM image of the nickel-coated aluminum microspheres shown in Example 1 of the present invention (a is a structural schematic diagram, and b is a SEM image of the nickel-coated aluminum microspheres); Figure 3 SEM and EDS elemental images of the nickel-coated aluminum microspheres shown in Example 1 of the present invention (a is a SEM image, b is an EDS element distribution image, c is an Al element distribution image, and d is a Ni element distribution image); Figure 4 SEM image of the boron nitride nanomaterial for metal reinforcement shown in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0022] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.

[0023] Example 1 Take 100g of nickel-coated aluminum microspheres with a particle size of 150μm, place the nickel-coated aluminum microspheres in an inert gas environment and heat them to 800℃, mix the gas BCl3 and methanol source with a molar ratio of 1:2, and pass them into the tube furnace to infiltrate nano-level boron on the surface of the nickel-coated aluminum microspheres, add the boronized nickel-coated aluminum microspheres to a stirring tank and stir for 30s to remove the peeled boron source. The structural diagram and SEM diagram of the nickel-coated aluminum microspheres are shown in Figure 2. Figure 2 and Figure 3 shown.

[0024] The boronized nickel-coated aluminum microspheres were placed in a tube furnace with 100 ml / min ammonia and 100 ml / min hydrogen, and annealed at 1190°C for 6 h to prepare a composite material of boron nitride nanosheets and boron nitride nanotubes. The SEM image is as follows: Figure 1 A 10 nm titanium metal coating was deposited on the surface of the composite nanotube, and then 60% aluminum powder was added, pressed into blocks at a pressure of 5 MPa, and annealed at 700 ° C to obtain the masterbatch of metal-reinforced boron nitride nanomaterials. The SEM of metal-reinforced boron nitride nanomaterials is shown in Figure 4 shown.

[0025] After adding this masterbatch to aluminum alloy, the strength of aluminum alloy increases by 50% and the elongation decreases by 10%.

[0026] Example 2 Take 100g of nickel-coated aluminum microspheres with a particle size of 300μm, place the nickel-coated aluminum microspheres in a tube furnace in an inert gas environment and heat them to 900℃, mix the gas BCl3 and ethanol source with a molar ratio of 1:2, and pass them into the tube furnace to infiltrate nano-level boron on the surface of the nickel-coated aluminum microspheres, add the boronized nickel-coated aluminum microspheres into a stirring tank and stir for 50s to remove the peeled boron source.

[0027] The boronized nickel-coated aluminum microspheres were placed in a tubular furnace with 40 ml / min ammonia and 260 ml / min nitrogen, and annealed at 1150 ° C for 6 hours to prepare a composite material of boron nitride nanosheets and boron nitride nanotubes. A 15 nm titanium metal coating was deposited on the surface of the composite nanotubes, and then 70% aluminum powder was added, pressed into blocks at 8 MPa pressure, and annealed at 750 ° C to obtain the masterbatch of boron nitride nanomaterials for metal reinforcement; after adding the masterbatch to aluminum alloy, the strength of the aluminum alloy increased by 68% and the elongation decreased by 8%.

[0028] Example 3 Take 100g of nickel-coated aluminum microspheres with a particle size of 50μm, place the nickel-coated aluminum microspheres in a tube furnace in an inert gas environment and heat them to 850℃, mix the gas BCl3 and propanol source with a molar ratio of 1:2, and pass them into the tube furnace to infiltrate nano-level boron on the surface of the nickel-coated aluminum microspheres, add the boronized nickel-coated aluminum microspheres into a stirring tank and stir for 30s to remove the peeled boron source.

[0029] The boronized nickel-coated aluminum microspheres were placed in a tube furnace with 150 ml / min ammonia and 50 ml / min argon, and annealed at 1250 ° C for 6 hours to prepare a composite material of boron nitride nanosheets and boron nitride nanotubes. A 15 nm titanium metal coating was deposited on the surface of the composite nanotubes, and then 75% aluminum powder was added, pressed into blocks at a pressure of 5 MPa, and annealed at 700 ° C. The masterbatch of boron nitride nanomaterials for metal reinforcement was obtained; after the masterbatch was added to aluminum alloy, the strength of the aluminum alloy increased by 90% and the elongation decreased by 12%.

[0030] Example 4 Take 100g of nickel-coated aluminum microspheres with a particle size of 500μm, place the nickel-coated aluminum microspheres in a tube furnace in an inert gas environment and heat them to 900℃, mix ammonia borane and methanol alcohol source gases with a molar ratio of 1:2, and pass them into the tube furnace to infiltrate nano-level boron on the surface of the nickel-coated aluminum microspheres, add the boronized nickel-coated aluminum microspheres into a stirring tank and stir for 50s to remove the peeled boron source.

[0031] The boronized nickel-coated aluminum microspheres were placed in a tubular furnace with 60 ml / min hydrogen and 140 ml / min ammonia, and annealed at 1130 ° C for 6 hours to prepare a composite material of boron nitride nanosheets and boron nitride nanotubes. A 5 nm titanium metal coating was deposited on the surface of the composite nanotubes, and then 90% aluminum powder was added, pressed into blocks at a pressure of 10 MPa, and annealed at 750 ° C. The masterbatch of boron nitride nanomaterials for metal reinforcement was obtained; after the masterbatch was added to aluminum alloy, the strength of the aluminum alloy increased by 80% and the elongation decreased by 11%.

[0032] The present invention relates to a preparation technology of boron nitride nanosheets and boron nitride nanotube composite nanotubes, which adopts magnesium powder and boron oxide as raw materials, ensures the continuous occurrence of gas phase reaction and liquid phase reaction by selecting a reasonable reaction interval, and synthesizes a large number of boron nitride nanosheets on the outer wall surface of the synthesized boron nitride nanotubes. The composite nanotubes can significantly reduce the agglomeration in the metal matrix casting process, form titanium boride, aluminum boride, and aluminum nitride nanoparticles by in-situ interface reaction, can inhibit the growth of metal grains, and avoid the burning of nanotubes, realize the synergistic enhancement of nanotubes and nanoparticles, can significantly improve the strength of metal matrix composite materials under the condition of low addition amount, and maintain good plasticity, good neutron absorption performance, and high temperature creep resistance. The preparation process greatly reduces the cost of raw materials, avoids the use of high energy consumption plasma method for preparation, and the prepared boron nitride nanosheets and boron nitride nanotube composite tubes have great application prospects in the field of metal reinforcement.

[0033] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres, characterized in that: The steps include: S1: The nickel-coated aluminum microspheres are heated in an inert gas, and a mixed gas of a gaseous boron source and a gaseous alcohol source is introduced to obtain boronized nickel-coated aluminum microspheres; S2: stirring the boronized nickel-coated aluminum microspheres obtained in step S1 to obtain nickel-coated aluminum microspheres from which the boron source has been removed; S3: annealing the nickel-coated aluminum microspheres obtained in step S2 with the boron source removed at high temperature in a mixed gas containing ammonia to prepare a composite material of boron nitride nanosheets and boron nitride nanotubes; S4: in situ depositing a nano-titanium metal coating on the surface of the composite material of boron nitride nanosheets and boron nitride nanotubes obtained in step S3 to obtain a composite material of boron nitride nanosheets and boron nitride nanotubes with a titanium layer; adding aluminum powder to the composite material of boron nitride nanosheets and boron nitride nanotubes with a titanium layer, pressing it into particles, and annealing it in an inert gas to obtain a boron nitride nanomaterial for metal reinforcement.

2. The method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres according to claim 1, characterized in that: In step S1, the particle size of the nickel-coated aluminum microspheres is 50-500 μm, the thickness of the nickel layer is 10 μm, and the morphology of the nickel-coated aluminum microspheres is spherical.

3. The method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres according to claim 1, characterized in that: The inert gas in step S1 is argon, and the argon pressure ranges from 0.01 to 0.1 MPa; And / or, the heating temperature in step S1 is 750-950° C.; And / or, the molar ratio of the gaseous boron source to the gaseous alcohol source in step S1 is 1:1.5-2.

5.

4. The method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres according to claim 1, characterized in that: The boron source in step S1 includes one or both of BCl3 and ammonia borane; And / or, the gaseous alcohol source in step S1 includes one or more of methanol, ethanol, and propanol.

5. The method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres according to claim 1, characterized in that: In step S2, the stirring speed of the boronized nickel-coated aluminum microspheres is 50 to 300 rpm, and the stirring time is 30 to 60 seconds.

6. The method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres according to claim 1, characterized in that: The mixed gas containing ammonia in step S3 includes ammonia and an inert gas, and the inert gas includes one or more of nitrogen, hydrogen, and argon; And / or, the annealing temperature of the high temperature annealing in step S3 is 900-1500° C., and the annealing time is 5.5-6.5 hours.

7. The method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres according to claim 1, characterized in that: In step S3, the boron nitride nanotubes in the composite material of boron nitride nanosheets and boron nitride nanotubes prepared have a tube length of 50-100 μm, a diameter of 150-200 nm, and a wall thickness of 30-80 nm.

8. The method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres according to claim 1, characterized in that: In step S3, the boron nitride nanosheets in the composite material of boron nitride nanosheets and boron nitride nanotubes prepared have a lateral length of 20-50 nm and a thickness of 10-20 nm.

9. The method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres according to claim 1, characterized in that: In step S4, the titanium layer thickness of the composite material of boron nitride nanosheets and boron nitride nanotubes having a titanium layer is 5 to 15 nm; And / or, the mass of the aluminum powder in step S4 is 50-90% of the mass of the composite material of boron nitride nanosheets and boron nitride nanotubes having a titanium layer; And / or, the pressure at which the aluminum powder is pressed into particles in step S4 is 2-10 MPa.

10. The method for in-situ preparation of metal-reinforced boron nitride nanomaterials on the surface of metal composite microspheres according to claim 1, characterized in that: The inert gas in step S4 is argon; And / or, the annealing temperature in the inert gas in step S4 is 650-800°C.